Representação da informação na catalogação na publicação: o serviço/produto da ficha catalográfica em bibliotecas universitárias - SILVA, Eddie Carlos Saraiva da (2023)
The study has as its object the cataloging form and extends to the services and informational products offered by Higher Education Institutions, either in the service of manual or automated cataloging forms. The motivation for choosing the topic was due to the perception of the organization of information made in catalog sheets of books and the perception that some users have a direct guide in the form for the elaboration of references and that for this it is necessary that the information is organized and standardized. The research is descriptive as to its objective, with a qualitative-quantitative approach and of a basic nature. The procedures used were bibliographic research to build the theoretical framework and it is based on the ideas and thoughts of authors such as Mey (1995), Borges (2019; 2020), Alves (2009) and, Lima and Alvares (2012). Documentary research was also carried out, such as the Anglo-American Code of Cataloging Code, Resolution n. 184/2017, of the Federal Council of Librarianship and the catalog sheets issued by the participating institutions. In addition, the application of an interview through an electronic form was necessary to build the profile of the librarians and institutions that participated and still have a personal point of view of the professionals who work with the preparation of the catalog, directly and indirectly. As initial results, we observed that most participants, all private HEIs, make use of the manual cataloging form, and the use of the automated service is up to the federal universities. The catalog card can be used both by users in the construction of consulted and cited references, as well as in the representation of information in electronic catalog systems used by libraries. It is also noteworthy the standardization of the elements present in a catalog card, where it was observed that many of the descriptive fields are shared by institutions in their model form, however, the same element ends up variations in the form it is presented. In the catalog card services provided by public and private HEIs in Pará, there is a variation in the application of the guidelines for the elaboration, although the source of guidance for the descriptive representation of the material is the same for all, the AACR2. In addition, the service is a product of the informational work of the librarian and most institutions still do not adopt CFB Resolution No. 184/2017, which makes the description of the name and registration of the information professional responsible for the form mandatory documents of any kind.